Superconductivity in Ti, Sb, Yb, Bi, Pb and Y multiply substituted TI1212 system / Wan Faizah Wan Abdullah - Wan Abdullah, Wan Faizah (2005)
The effects of the elemental substitution on the 1212 phase formation and superconducting properties of (Tl,Bi)(Sr,Ti)2Ca0.9Y0.1Cu2O7 and (Tl,Pb)(Sr,M)2CaCu2O7 (M = Yb, Sb) series have been investigated. The samples were prepared using high purity oxides by solid state and precursor method. Crystal structures of the samples were analyzed using X-ray powder diffraction method while microstructures were investigated by scanning electron microscope (SEM). Measurements of electrical resistance were carried out using standard four-pointprobe method. Powder X-ray diffraction patterns for Tl0.9Bi0.1Sr2-yTiyCa0.9Y0.1Cu2O7 (y = 0 – 0.5) with Bi, Ti and Y triple substitution revealed that all the samples consist mostly of major 1212 and minor 1201 crystalline phases. Temperature dependent resistance measurements on Tl1-xBixSr1.9Ti0.1Ca0.9Y0.1Cu2O7 (x = 0 – 0.6) showed optimum superconductivity for x = 0.3 with Tc onset of 93.3 K and Tc zero of 68.2 K Temperature dependent electrical resistance measurements on Tl1-mPbmSr1.8Yb0.2CaCu2O7 (m = 0.1– 0.5) showed metallic normal state behaviors and increase in Tc zero from 61.1 K at m = 0.1 to a maximum value of 101.1 K at m = 0.5. Substitutions of Yb at Sr-site of Tl0.5Pb0.5Sr2-nYbnCaCu2O7 with n = 0 – 0.6 increased value of in Tc zero from 62.2 K at n = 0 to a maximum value of 101.1 K at n = 0.2. Substitution of Pb at Tl-site and Sb at Sr-site in Tl1-qPbqSr1.8Sb0.2CaCu2O7 (q = 0.1 – 0.6) promote 1212 phase formation and increased in Tc zero from 26.1 K at q = 0.1 to 80.2 K at q = 0.5. From this study, it is found that apart from the Tl and Ca sites, Sr-site substitution is also effective in optimizing critical temperature, Tc and critical current density, Jc of Tl1212 samples. The results were discussed in terms of the concept of average copper valence and ionic radius of elements. i